Auditor Quantitative Materiality Disclosure, Earnings Management Concerns, and Generation Z Investors’ Willingness to Invest: An Experimental Study - Nurul Mustafida; Luciana Spica Almilia; Lufi Yuwana Mursita; Kadek Pranetha Prananjaya; Titis Puspitaningrum Dewi Kartika (Universitas Trunojoyo Madura, 2026)
The debate over mandating quantitative materiality disclosure in the auditor’s report has persisted for several years, prompting numerous studies on its potential outcomes. Given the increasing involvement of Generation Z in capital markets, this study employs an experimental design to retest prior findings on the effect of auditor quantitative materiality disclosure on Generation Z investors’ willingness to invest. Specifically, this study examines whether this demographic is influenced by both auditor quantitative materiality disclosure and concerns about earnings management in their investment decisions. Using data from an experiment involving 101 university students, the results are consistent with the prior literature, suggesting that quantitative materiality disclosure generally reduces the willingness to invest. Furthermore, a simple effects test reveals that when concerns about earnings management are high, Generation Z investors show reduced willingness to invest when quantitative materiality disclosure is present. In contrast, this effect is not found when concerns about earnings management are low. These findings offer insights into how Generation Z investment decisions are shaped by quantitative and qualitative risk assessments.